Voltammetric Studies and Micro Level Determination of Arsenic in Aqueous Matrices - Bais, Rajni; Rathore, Parul; Tiwari, Mukesh (Asian Journal of Chemistry, 2015)
A differential pulse polarographic method for the trace determination of arsenic is presented. The preliminary investigations have indicated the suitability of a complexing media of 0.01 M citric acid in 0.01 M sodium acetate, where As(III) showed a sharp DP reduction peak at -0.93V vs SCE. Linearity of the calibration curve was achieved upto 8.5 ppm with a detection limit of 0.009 μg/mL. The coexisting metal ions such as Cu(II), Pb(II), Cd(II) and Zn(II) did not interfere. The differential pulse polarogram method has been applied successfully for the determination of arsenic contents in industrial wastes analysis.